Pengaruh City Branding terhadap Keputusan Berkunjung Wisatawan pada Wisata Religi Makam Gus Dur di Kabupaten Jombang - Abid Datul Mukhoyaroh; Luluk Nur Hidayati (Fakultas Ekonomi Universitas 45 Surabaya, 2021)
The best way to encourage competitiveness among regions one of which create a strong brand identity to reflect the region to attract potential consumers, tourists, investors or residents. One of the marketing activities to promote the City. Branding today is through tourism activities. This study aims to find and analyze the effect of the decision of City Branding travelers visiting the tomb of religious tourism Gus Dur in Jombang. This type of research used in this research is quantitative with survey approach. The analysis technique used is multiple linear regression analysis with six predictor obtained as follows, obtained partial test t value for X1 = 0.134, X2 = - 2.826, X3= -0.108, X4 = 2.385, X5 = 5.965, X6 = -0, 26 meaning that the variable X1 is not partial effect on variable Y, X2 partial effect on variable Y, X3 is not partial effect on variable Y, the variable X4 partial effect on variable Y, variable X5 partial effect on variable Y, variable X6 is not partial effect to variable Y.